AC-Based Differential Evolution Algorithm for Dynamic Transmission Expansion Planning - Ibrahim Alhamrouni; Mohamed Salem; Azhar Bin Khairuddin; Jamilatul Lilik; Awang Jusoh; T. Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This work proposes a method based on a mixed integer nonlinear non-convex programming model to solve the multistage transmission expansion planning (TEP). A meta-heuristic algorithm by the means of differential evolution algorithm (DEA) is employed as an optimization tool. An AC load flow model is used in solving the multistage TEP problem, where accurate and realistic results can be obtained. Furthermore, the work considers the constraints checking and system violation such as real and power generation limits, possible number of lines added, thermal limits and bus voltage limits. The proposed technique is tested on well known and realistic test systems such as the IEEE 24 bus-system and the Colombian 93-bus system. The method has shown high capability in considering the active and reactive power in the same manner and solving the TEP problem. The method produced improved good results in a fast convergence time for the test systems.